Results of tension band wiring in intra-articular collateral ligament avulsion fractures of the phalanx - Manandhar, Rajeev Raj; Lakhey, Shishir; Karki, Umash (Journal of Kathmandu Medical College, 2018)
Background: Avulsion fractures of the base of proximal phalanx associated with ulnar or radial collateral ligament instability are relatively rare. The small size of the fragment and strong deforming pull of the attached soft tissues make the process of reduction and maintenance difficult.Objective: The purpose of this study was to assess the functional outcome of tension band wiring in intra-articular avulsion fractures of the base of the proximal phalanx.Methodology: A prospective study was performed on ten patients with intra-articular collateral ligament avulsion fractures of the proximal phalanx (Jupiter’s classification Type III). A tension band construct was performed using a dorsal approach. The functional outcome was assessed at six months with the quick Disability of Arm, Shoulder and Hand score.Results: The mean age of the patients was 25.8 years (Mean ± SD: 25.80). Six avulsion fractures were of the ulnar collateral ligament of the proximal phalanx of the index finger, one involved the radial collateral ligament of the ring finger and three, the radial collateral ligament of the little finger suggesting an abduction injury. All fractures had united at three months. Eight patients were graded as excellent and two as good. All patients were satisfied with the surgery and the functional outcome of the injured digit. There were no perioperative complications.Conclusion: The functional outcome of tension band wiring in intra-articular collateral ligament avulsion fractures of the base of the proximal phalanx was good to excellent.